Influence of Corporate Social Responsibility on Financial Performance of Listed Manufacturing Firms in Kenya - Nzuki, Judith Mbula; Opuodho , Gordon.O. (International Journal of Finance, 2022)
Purpose: The general objective of the study was to establish the influence of corporate social responsibility on financial performance of listed manufacturing firms in Kenya. The specific objectives of the study was to establish the influence of environmental responsibility, CSR initiative on public education, corporate philanthropy on financial performance of listed manufacturing firms in Kenya. The theories that anchored the study comprised of Triple Bottom Line Theory, Integrative Social Contracts Theory and The Stakeholder Theory. Methodology: A descriptive research design was employed in the study and the target population comprised of ten listed manufacturing firms in Kenya. The units of observation comprised of employees from upper, middle and lower management levels. A total of 90 employees were targeted. The study used questionnaires to gather primary data and secondary data was acquired from financial reports of the selected firms. Both descriptive and inferential statistics were employed in analyzing the collected data. The statistics were generated through Statistical Package for Social Scientists and MS Excel. Results: The findings of the study revealed that environmental responsibility and corporate philanthropy bears a positive and significant influence on the levels of financial performance of listed manufacturing firms. This is shown by beta values of 0.197 and 0.271 and significant values of 0.0122 and 0.0136 respectively. The results implies that increasing either environmental responsibility or corporate philanthropy with one unit results to increase in the levels of financial performance of listed manufacturing firms in Kenya with respective beta values. The study further revealed that CSR initiative on public education bears a positive but insignificant influence on financial performance of listed manufacturing firms in Kenya. This is shown by a beta value of 0.101 and an insignificant value of 0.0743. This bears the implication that increasing CSR initiative on public education with one-unit results to insignificant increase in the levels of financial performance of the listed manufacturing firms. Unique Contribution to Theory, Policy and Practices: The study recommended the listed manufacturing in Kenya to enhance both environmental responsibility and corporate philanthropy practices in the firm's operations since the practices increases the financial performance levels to a positive and significant level.